The winged colt of Casa Mia - Byars, Betsy Cromer; Cuffari, Richard (New York : Avon, 1975)
It looks like a long summer for both of them when Charles is sent to spend it with Uncle Coot, but then a colt is born with wings!
4.0
3-6
3-6
New York Times
Keywords: Fantasy; Fantasy fiction; Texas -- Fiction; Texas -- Fiction